PELATIHAN SABLON DTF PADA SISWA DESAIN KOMUNIKASI VISUAL - Setia, Diana; Adi, Ananda; Alvianzah, Muhammad (Mafaza : Jurnal Pengabdian Masyarakat, 2025)
Tuban is a regency located on the North Coast of Java, consisting of 20 sub-districts and the capital city is Tuban District. There are three vocational high schools in this district. One of them is Sekolah Menengah Kejuruan 2 Tuban or SMK N 2 Tuban for short. This school is located in Tuban Regency. SMK N 2 Tuban has several departments, one of which is Visual Communication Design department which has been established for three years. There are many activities carried out by the Visual Communication Design department, one of which is the DTF screen printing training using logotype. The method used is training and mentoring method. The approach used during the implementation of mentoring activities is to use a service learning approach. The results of this community service research are: 1) students of SMKN 2 Tuban majoring in DKV understand and know DTF screen printing techniques, 2) students of SMKN 2 Tuban are able to make DTF screen printing, 3) students of SMKN 2 Tuban majoring in DKV are motivated to create creative industries in the field of DTF screen printing. It is hoped that this training can add insight for students and later become a business opportunity to increase economic value for them.